LANGUAGE IDEOLOGY OF TEENAGERS TOWARD THE CATEGORIES OF GENDER IN LANGSA KOTA - Cut Kania Annissa Jingga Muti; Nisa Faradilla; Sarah Ziehan Harahap (Universitas Islam Sumatera Utara (UISU), 2018)
ABSTRAKSociolinguistics is a study or discussion of language related to the language Sociolinguistics consists of two elements of the word that is socio and linguistics. Linguistics is the study of language, especially the elements of language (speech, word, sentence) and the relationship between speakers who are part of the members of society.Sociolinguistics places the position of language in relation to its use in society. This means that sociolinguistics views language as primarily a social system and communication system, and is part of a particular society and culture. Hence language and use of language are not observed individually but are always associated with their activities in society.Every human being born into the world is elected into two types, women and men. Gender refers to differences in male and female characters based on cultural construction, relating to the nature of their status, position, and role in society as well as socially-culturally constructed gender differences.In sociolinguistics, language and gender have a very close relationship. There is the phrase